El estado y las autonomías : treinta aǫs después / José Vidal Pelaz López (dir.) ; Leopoldo Calvo-Sotelo Ibáęz Martín ... [et al.] - Pelaz López, José-VidalCalvo-Sotelo Ibáęz Martín, Leopoldo (Historia y sociedad; 149)
Bibliografía: p. [151]-165